Pengaruh Costumer Review dan Influencer Review Pada Niat Beli di Aplikasi Shopee dengan Kepercayaan sebagai Variabel Moderasi - Hamdani; Lukitaningsih, Ambar; Ningrum, Nonik Kusuma (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to investigate the impact of customer reviews and Influencer reviews on purchase intention and the mediating role of trust in the relationship. A quantitative study was conducted. Two hundred respondents from students who live in Yogyakarta consist of five districts: The cities of Yogyakarta, Bantul, Sleman, Gunung Kidul, and Kulon Progo. divided into two groups to self-assess their opinions on customer reviews, Influencer reviews, trust, and purchase intent. The collected data were analyzed using the Statistical Program for Social Science (SPSS) using SPSS version 25.00. The results of the study show that Influencer Reviews and Customer Reviews have a positive effect on purchase intentions. On the other hand, trust failed to moderate Customer Reviews and failed to show its effect. However, Trust Moderates Influencers' Purchase Intentions and strengthens significantly and positively. Trust as a moderating variable is also validated in this study.